EVALUATION OF COST-EFFECTIVENESS OF PLATELET REACTIVITY ANALYSIS USING THE VERIFYNOW P2Y12 ASSAY IN PATIENTS AFTER ACUTE CORONARY SYNDROME - A. V. Rudakova; N. V. Lomakin (Столичная издательская компания, 2015)
Dual antiplatelet therapy, including clopidogrel and aspirin, in a significant share of patients after acute coronary syndrome (ACS) is characterized by high level of platelet reactivity, which is associated with an increased incidence of cardiovascular events. Perhaps it will make reasonable the prescription of new antiplatelet drugs, particularly the combination of ticagrelor with aspirin.Aim. To assess the cost-effectiveness of VerifyNow P2Y12 platelet reactivity testing in patients after ACS.Material and methods. The analysis was performed for patients aged 55 years after ACS by modeling based on the results of the PLATO trial considering Russian epidemiological data. The time horizon of simulation was 5 years. It was assumed that the patients were receiving either generic clopidogrel or ticagrelor for 1 year, or before maintenance treatment VerifyNow P2Y12 assay had been performed, and the patients with platelet reactivity index >230 24-48 hours after ACS were receiving ticagrelor and the remaining patients - generic clopidogrel. It was expected that after 1 year the patients would discontinue treatment with clopidogrel or ticagrelor, and hereafter additional therapeutic effect of their use would be absent. The costs of antiplatelet agents in the reference case corresponded to the weighted average price of public procurement in 2013 in Russia. The costs of treatment of complications corresponded to the compulsory health insurance rates for St. Petersburg in 2014. The cost and life expectancy were discounted at 3.5% per year.Results. The platelet reactivity test and the prescription by its results of the combination of clopidogrel plus aspirin or ticagrelor plus aspirin can prevent 5 myocardial infarction and 6 deaths per 1000 patients additionally as compared with the prescription of clopidogrel plus aspirin combination to all patients. The costs for one additional year of life as compared with the combination of clopidogrel plus aspirin were 376.5 and 373.2 thousand rubles, respectively, the costs for one additional quality adjusted life year (QALY) were 433.8 and 509.8 thousand rubles, respectively. The total predictive value of costs per 1 patient with ACS using the test was 32% lower than in the routine use of ticagrelor in all patients.Conclusion. Assessment of platelets reactivity using VerifyNow P2Y12 assay in patients with ACS and modification of antithrombotic therapy in accordance with the received data can be considered as a cost-effective intervention which can reduce treatment costs as compared with the routine use of new antithrombotic drugs.